Caring for Tube‐Fed Children: A Review of Management, Tube Weaning, and Emotional Considerations. (19th March 2015) - Edwards, Sarah; Davis, Ann M.; Bruce, Amanda; Mousa, Hayat; Lyman, Beth; Cocjin, Jose; Dean, Kelsey; Ernst, Linda; Almadhoun, Osama; Hyman, Paul
Abstract : Enteral nutrition is the practice of delivering nutrition to the gut either orally or through a tube or other device. Many children are reliant on enteral feedings to either supplement their nutrition or as a complete source of their nutrition. Managing children on tube feedings requires a team of providers to work through such dilemmas as feeding schedules, weaning from tube feeding, sensory implications of tube feeding, treatment of pain or nausea associated with eating, oral‐motor issues, and behavioral issues in the child and family. The purpose of the current review is to summarize the multidisciplinary aspects of enteral feeding. The multidisciplinary team consists of a variable combination of an occupational therapist, speech‐language pathologist, gastroenterologist, psychologist, nurse, pharmacist, and dietitian. Children who have minimal oral feeding experience and are fed via a nasogastric or gastrostomy tube often develop oral aversions. Limited data support that children with feeding disorders are more likely to have sensory impairment and that early life pain experiences contribute to feeding refusal. There are inpatient and outpatient programs for weaning patients from tube feeding to eating. The parent‐child interaction is an important part of the assessment and treatment of the tube‐fed child. This review also points out many information gaps, including data on feeding schedules, blenderized tube feedings, the best methods for weaning children off enteral feedings, the efficacy of chronic pain medications with tube‐fed children, and, finally, the necessity of the assessment of parental stress among all parents of children who are tube fed.